Effect of personal and work stress on burnout, job satisfaction and general health of hospital nurses in South Africa - Khamisa, Natasha; Peltzer, Karl; Ilic, Dragan; Oldenburg, Brian (Health SA = SA Gesondheid, 2017)
The majority of studies to date have focused on the effects of work stress in the nursing environment, with the effect of personal stress in nursing being less explored. This study sought to determine whether personal stress is a more significant predictor of burnout, job satisfaction and general health than work stress. Of the 1200 nurses randomly selected to participate in the study, 895 agreed to complete six questionnaires over 3 weeks. Data was analysed using hierarchical multiple linear regression. Findings revealed that personal stress is a better predictor of burnout and general health than job satisfaction, which is better predicted by work stress. The findings of this study could inform potential solutions to reduce the impact of personal and work stress on burnout, job satisfaction and general health. Coping strategies and staffing strategies need to be evaluated within developing contexts such as South Africa to ascertain their effectiveness.